A discussion frame for explaining records that are based on algorithmic output. (18th November 2019) - Andresen, Herbjørn
Abstract : Purpose: The purpose of this paper is to raise attention within the records management community about evolving demands for explanations that make it possible to understand the content of records, also when they reflect output from algorithms. Design/methodology/approach: The methodological approach is a conceptual analysis based in records management theory and the philosophy of science. The concepts that are developed are thereafter applied to "the right to an explanation" and "an algorithmic ethics approach, " respectively, to further examine their viability. Findings: Different forms of explanations, ranging from "certain" explanations to predictions, as well as varying degrees of control over the input data to algorithms, affect the nature of the explanations and what kinds of records the explanations may reside in. Originality/value: This paper contributes to a conceptual frame for discussing where explanations to algorithms may be documented, within different kinds of records, emanating from different kinds of processes.